2003
DOI: 10.1002/jmv.10391
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human metapneumovirus in Japan

Abstract: A new human pneumovirus, provisionally designated human metapneumovirus, was discovered by Dutch researchers. We examined 142 serum samples from the general population aged from 1 month to 35 years in Japan for human metapneumovirus antibody by indirect immunofluorescence assays using human metapneumovirus-infected monkey kidney cells. The overall prevalence of human metapneumovirus infection was 72.5%. The seropositive rate was lowest in the age group of 6 months to 1 year and gradually increased with age. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 10 publications
7
124
1
5
Order By: Relevance
“…Nearly all children have serologic evidence of infection by 5 y of age (1,32). van den Hoogen et al (1) originally found no hMPV in 400 samples obtained from asymptomatic children, whereas a group led by Williams tested 86 samples from asymptomatic children found only one positive sample for hMPV (1%) (2).…”
Section: Human Metapneumovirusmentioning
confidence: 99%
“…Nearly all children have serologic evidence of infection by 5 y of age (1,32). van den Hoogen et al (1) originally found no hMPV in 400 samples obtained from asymptomatic children, whereas a group led by Williams tested 86 samples from asymptomatic children found only one positive sample for hMPV (1%) (2).…”
Section: Human Metapneumovirusmentioning
confidence: 99%
“…Since hMPV was first reported (van den Hoogen et al, 2001) in 2001, much progress has been made in its detection Ebihara et al, 2003Ebihara et al, , 2004Hamelin and Boivin, 2005;Leung et al, 2005;Mackay et al, 2003;Maertzdorf et al, 2004), in understanding its genetic diversity Falsey et al, 2003;Ludewick et al, 2005;Mackay et al, 2003) and in documenting its varied clinical presentation (Falsey et al, 2003;Principi et al, 2006). By linking demographic and clinical data to a large, 3-year, viral culture specimen repository, we sought to describe hMPV infections among patients evaluated by a large US Midwestern referral laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…19 Meanwhile, there have been several reports regarding the seroprevalence of hMPV infection around the world. Almost all people acquire seropositivity for hMPV by the age of 10 years, 2 and hMPV is known to infect individuals repeatedly throughout adult life and into old age. [5][6][7][8][9] Although there are no reports of IgG titer differences between patients with hypertension and normotensive controls after individual infections with pathogens, including hMPV, it is possible that hypertension itself may increase the anti-IgG titer in response to repeated hMPV infections in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…1 This virus is a member of the genus metapneumovirus of the subfamily Pneumovirinae of the family Paramyxoviridae. hMPV induces infections of the lower respiratory tract, including bronchitis, bronchiolitis and pneumonia, in young children 2 and immunocompromised individuals, 3 along with upper respiratory tract illnesses and influenza-like illness. 4 In January 2005, we reported an outbreak of nosocomial hMPV infection in elderly subjects in a long-term care facility (LTCF) in Japan.…”
Section: Introductionmentioning
confidence: 99%